2022
DOI: 10.1212/wnl.0000000000012967
|View full text |Cite
|
Sign up to set email alerts
|

Serum Neuron-Specific Enolase Thresholds for Predicting Postcardiac Arrest Outcome

Abstract: Background and ObjectivesTo determine thresholds of serum neuron-specific enolase (NSE) for prediction of poor outcome after cardiac arrest with >95% specificity using a unique method of multiple thresholds meta-analysis.MethodsData from a systematic review by the European Resuscitation Council (ERC 2014) were updated with literature searches from PubMed, Cochrane, and Scopus until August 2020. Search terms included the MeSH terms “heart arrest” and “biomarkers” and the text words “cardiac arrest,” “neuron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…This reflects findings of a previous study that suggested a certain cutoff value of serum NSE with respect to evaluating neurological outcomes in patients with OHCA (based on the lower limit of the 95% CI for serum NSE obtained within 24 hours of OHCA). [ 18 ] The subgroup analysis in the current study showed numerically improved AUROC values for serum S100B with respect to predicting BBB disruption (AUROC, 0.718–0.836) and a 0% false-positive ratio for predicting abnormal Qa. Moreover, we found an approximately 3.5-fold increase in the coefficient of determination between serum S100B and Qa (R 2 , 0.110–0.382).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…This reflects findings of a previous study that suggested a certain cutoff value of serum NSE with respect to evaluating neurological outcomes in patients with OHCA (based on the lower limit of the 95% CI for serum NSE obtained within 24 hours of OHCA). [ 18 ] The subgroup analysis in the current study showed numerically improved AUROC values for serum S100B with respect to predicting BBB disruption (AUROC, 0.718–0.836) and a 0% false-positive ratio for predicting abnormal Qa. Moreover, we found an approximately 3.5-fold increase in the coefficient of determination between serum S100B and Qa (R 2 , 0.110–0.382).…”
Section: Discussionmentioning
confidence: 61%
“…Thus, we performed a subgroup analysis in patients with serum NSE levels of <40.8 ng/mL measured simultaneously with S100B, as suggested according to the lower limit of the 95% confidence interval (CI) for serum NSE obtained within 24 hours following cardiac arrest within a recent meta-analysis. [ 18 ] We performed this subanalysis to estimate the relationship between serum S100B and BBB status after excluding the confounding effects of established neuronal cell injury.…”
Section: Methodsmentioning
confidence: 99%
“…We suggest that it may be advantageous to also determine neuron-specific enolase (NSE) in plasma/serum. When hemolytic samples are excluded, NSE already established as a prognostic marker in hypoxic brain injury ( Sharma et al, 2022 ; Kim et al, 2023 ) probably is a valuable tool for the quantification of neuronal injury in septic encephalopathy of older persons.…”
Section: Conclusion and Suggestions For Future Researchmentioning
confidence: 99%
“…A post hoc analysis of the Targeted Temperature Management trial revealed that neurofilament levels were 13× higher in patients with malignant versus benign electroencephalographic patterns, and the extent of brain injury was more strongly related to background rather than superimposed discharges. 15 Imaging (eg, magnetic resonance-spectroscopy 16 ) and serological (eg, neuron-specific enolase 17 ) biomarkers for neuroprognostication are also valuable. Ultimately a multimodal approach will likely facilitate deep phenotyping enabling more robust neuroprognostication and targeted treatment strategies.…”
Section: Cardiac Arrestmentioning
confidence: 99%